The Extracellular Domains of IgG1 and T Cell-Derived IL-4/IL-13 Are Critical for the Polyclonal Memory IgE Response In Vivo - Turqueti-Neves, Adriana; Otte, Manuel; Schwartz, Christian; Schmitt, Michaela; Lindner, Cornelia; Pabst, Oliver; Yu, Philipp; Vöhringer, David (Plos Biology, 2015)
IgE-mediated activation of mast cells and basophils contributes to protective immunity against helminths but also causes allergic responses. The development and persistence of IgE responses are poorly understood, which is in part due to the low number of IgE-producing cells. Here, we used next generation sequencing to uncover a striking overlap between the IgE and IgG1 repertoires in helminth-infected or OVA/alum-immunized wild-type BALB/c mice. The memory IgE response after secondary infection induced a strong increase of IgE+ plasma cells in spleen and lymph nodes. In contrast, germinal center B cells did not increase during secondary infection. Unexpectedly, the memory IgE response was lost in mice where the extracellular part of IgG1 had been replaced with IgE sequences. Adoptive transfer studies revealed that IgG1+ B cells were required and sufficient to constitute the memory IgE response in recipient mice. T cell-derived IL-4/IL-13 was required for the memory IgE response but not for expansion of B cells from memory mice. Together, our results reveal a close relationship between the IgE and IgG1 repertoires in vivo and demonstrate that the memory IgE response is mainly conserved at the level of memory IgG1+ B cells. Therefore, targeting the generation and survival of allergen-specific IgG1+ B cells could lead to development of new therapeutic strategies to treat chronic allergic disorders.
EVALuna2:25871